URBAN UPGRADE IN BISKRA’S SHANTYTOWNS SAMPLE: THE NEIGHBORHOODS OF SIDI GHAZEL AND SIDI ROUAG (ALGERIA) - Djouheina Kouidre BOUHKELIFI; Fateh MEZERDI (Analele Universităţii din Oradea: Seria Geografie)
The shantytowns or slum area started to appear in the urban fabric within town zones in Algeria during the colonial period. This situation endured after the independence, in particular during the seventies of the last century. The reasons : a population growth and an increasing urbanization in big and intermediate cities, in addition to the industrial establishment resulting from the development choices. This latter wasn’t supported by balanced development. The impact was obvious on the urban development of the Algerian cities. Hence, the slum areas increased outside the town urban perimeter, where the public lands and the lands inconvenient for urbanization such as river shores, old quarries and hills. The citizen, in cause of that, stood in a permanent conflict with the relevant authorities, in particular municipalities, to settle the situation or to remove definitively the house. Hence, this situation leads to a degradation in the urban fabric and planning of numerous cities. The Governorate of Biskra was also affected by this phenomenon starting from the 1970s. It results, among other reasons, from its elevation to the status of Governorate in 1974 following the second administrative structuring in Algeria after the independence.